The Effect of Discovery Learning Model on Writing Ability of Descriptive Text at Grade XI SMAN 3 Tanjung Balai Academic Year 2025/2026 - Ayu Mulyani; Yen Aryni (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to examine the effect of Discovery Learning Model on students’ ability in writing Descriptive Text. This research employed a quantitative approach with an experimental design. It was conducted at SMA Negeri 3 Tanjungbalai involving 64 eleventh-grade students as the sample, consisting of 32 students in the experimental group (XI-1) and 32 students in the control group (XI-2). The experimental group was taught using the Discovery Learning Model, while the control group received conventional teaching. The data were collected through pre-test and post-test.The findings showed that the mean score of the experimental group increased from 62.3 in the pre-test to 84.8 in the post-test, indicating an improvement of 22.5%. Meanwhile, the control group showed a lower improvement from 55.9 to 65.7, with an increase of 9.8%. Furthermore, the result of the t-test revealed that the t-observed value (18.8) was higher than the t-table value (2.00) at the significance level of 0.05 with 62 degrees of freedom. This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In conclusion, the implementation of the Discovery Learning Model has a significant positive effect on students’ ability in writing Descriptive Text.